The agriculture-nutrition-income nexus in Tonga - Ma’asi, Losaline; Francis, Judith Ann (Technical Centre for Agricultural and Rural Cooperation, 2020)
Increasing reliance on imported foods, limited access to affordable nutritious local foods, and exposure to climate change and natural disasters are negatively impacting the health, well-being and livelihoods of Tongans. More than 50% of agricultural land is fallow. Oceanic and coastal fisheries resources are being depleted. The private sector is reluctant to increase investments in food processing facilities. 99% of the population is at high or moderate risk of developing noncommunicable diseases (NCDs); obesity, cardio-vascular disease, diabetes and hypertension are prevalent. Limited coordination exists among the various agencies implementing policies and programmes that address the agriculture, food and nutrition challenges. Key recommendations are give in this Technical Brief to meet the above challenges.